Hubungan antara Kecemasan Kesehatan dan Intensitas Penggunaan Media Sosial dengan Cyberchondria pada Generasi Z - Muhamad Ulul Azmi (Social Science Academic, 2026)
Cyberchondria refers to excessive and repetitive online health information seeking that paradoxically amplifies concern about one’s own health. Mainstream literature positions health anxiety as its strongest predictor, yet evidence from non-Western digital native populations remains limited. This study examined the relationship of health anxiety and social media use intensity with cyberchondria among Generation Z. A quantitative correlational design was applied to 358 participants aged 15–28 years in an Indonesian metropolitan area, recruited through purposive sampling. Data were collected using an adapted Cyberchondria Severity Scale, the Short Health Anxiety Inventory, and a social media use intensity scale based on Ellison’s aspects, with reliability coefficients of .923, .924, and .969 respectively. Data were analysed using Spearman’s rho correlation. Results showed that health anxiety was not significantly related to cyberchondria (rs = –.008; p = .880), whereas social media use intensity showed a significant positive relationship of moderate to strong magnitude (rs = .582; p < .001). Comparison of the two coefficients reveals the dominance of the external factor over the internal one. These findings indicate a shift in the entry point of the cyberchondria cycle among digital natives, from internal psychological vulnerability toward digital environmental exposure.